2018
DOI: 10.1007/s00436-018-5915-6
|View full text |Cite
|
Sign up to set email alerts
|

A lentiviral vaccine expressing KMP11-HASPB fusion protein increases immune response to Leishmania major in BALB/C

Abstract: Hydrophilic acylated surface protein B (HASPB) is an immunogenic Leishmania-specific protein that antibodies are produced against it in the sera of Leishmania-infected individuals. Kinetoplastid membrane protein 11 (KMP11) is another Leishmania antigen and considered as the suitable candidate for vaccine development Leishmaniasis. It is a highly conserved surface protein expressed in both promastigotes and amastigotes. In this study, KMP11 and HASPB coding sequences were cloned into a pCDH-cGFP lentiviral vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…In our previous study, immunogenicity evaluation of the whole protein of KMP11 and HASPB against L. major was successful in the BALB/c mice (14). Therefore, in this study, for the rst time, the immunogenicity of the KMP11 and HASPB as selected epitopes of the L-major was evaluated as a novel lentiviral multi-epitope vaccine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous study, immunogenicity evaluation of the whole protein of KMP11 and HASPB against L. major was successful in the BALB/c mice (14). Therefore, in this study, for the rst time, the immunogenicity of the KMP11 and HASPB as selected epitopes of the L-major was evaluated as a novel lentiviral multi-epitope vaccine.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous studies, we found that the lentiviral vaccine containing the kinetoplastid membrane protein 11 (KMP11) and hydrophilic acylated surface protein B (HASPB) whole proteins are capable of stimulating the immune system in the BALB/c mice (14). Therefore, in this study, the immunogenic effects of the epitopes of these two antigens were investigated.…”
Section: Introductionmentioning
confidence: 97%
“…145 A fusion of the kinetoplastid membrane protein 11 (KMP11) and hydrophilic acylated surface protein B (HASPB) genes was cloned into a lentiviral vector (pCDH-cGFP) that generated a protective response with significant increases in both pro-and antiinflammatory markers (IFN-γ and IgG2a versus IL-10 and IgG1). 146 The higher levels of IFN-γ and IgG2a indicated skewing toward a desirable Th1 response.…”
Section: Third Generation Vaccinesmentioning
confidence: 99%
“…Understanding the host defense mechanism against the parasite is essential in the production of an effective vaccine. Studies on leishmaniasis have shown that stimulation of cellular immunity is essential for defense against the parasite (8). Once the parasite enters the host, macrophages M1 or M2 play a key role in the parasite's defense or survival.…”
Section: Introductionmentioning
confidence: 99%